2018
DOI: 10.1002/ajoc.201800390
|View full text |Cite|
|
Sign up to set email alerts
|

Open‐Shell Characters, Aromaticities and Third‐Order Nonlinear Optical Properties of Carbon Nanobelts Composed of Five‐ and Six‐Membered Rings

Abstract: Geometric features, electronic structures and third‐order nonlinear optical (NLO) properties of belt‐shaped hydrocarbons, namely, carbon nanobelts, are investigated by using the density functional theory (DFT) methods. A carbon nanobelt composed of five‐ and six‐membered rings (IF‐CNB, 42π), which involves repeating indenofluorene (IF) units, is expected to exhibit both open‐shell multiradical character and relatively strong aromatic nature in the singlet state, while that composed only of six‐membered rings (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…[1][2][3]15 A particular class of CLPs is represented by an extension of indenofluorene 16 into a polymer, that is poly(indenoindene) (PInIn), where the alternation of five-and six-membered rings gives rise to the ladder structure. [17][18][19][20] The synthesis of PInIns was pioneered by Scherf and Müllen in 1992, but the final dehydrogenation step did not proceed completely, and unambiguous structural proof could not be obtained. 21 More recently, Wu et al synthesized a short segment of PInIn with four and five pentagons and hexagons, respectively, 17 but more extended PInIns have remained elusive.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…[1][2][3]15 A particular class of CLPs is represented by an extension of indenofluorene 16 into a polymer, that is poly(indenoindene) (PInIn), where the alternation of five-and six-membered rings gives rise to the ladder structure. [17][18][19][20] The synthesis of PInIns was pioneered by Scherf and Müllen in 1992, but the final dehydrogenation step did not proceed completely, and unambiguous structural proof could not be obtained. 21 More recently, Wu et al synthesized a short segment of PInIn with four and five pentagons and hexagons, respectively, 17 but more extended PInIns have remained elusive.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…In the original article, we reported that electronic structures and optical and magnetic response properties of an open‐shell carbon nanobelt (IF‐CNB) are evaluated by the spin‐unrestricted density functional theory (U‐DFT) method using the long‐range corrected LC‐BLYP exchange correlation functional, namely, at the LC‐UBLYP/6‐311+G** level. However, only in the calculations of magnetic response properties, we found that the results are obtained by the spin‐restricted DFT (R‐DFT) solution with < S 2 >=0.…”
Section: Figurementioning
confidence: 99%
“…[30][31][32][33][34] Nakano group reported the diradical characteristics and third-order NLO properties of openshell carbon nanobelts and carbon nanotubes. [35][36][37] Qiu group reported second-order NLO properties based on Pb(II)CPP. 38,39 Noteworthy, Du group successfully synthesized the first sp 2hybridized all-phenylene siamese-twin bismacrocycle SCPP [10] in 2021.…”
Section: Introductionmentioning
confidence: 99%